STRATEGI GURU DALAM PENGELOLAAN KELAS PADA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SEKOLAH MENENGAH PERTAMA NEGERI 1 LAMONGAN - Sa'arani, Nurhidayah Firdaus; Hunaida, Wiwin Luqna (AHSANA MEDIA: Jurnal Pemikiran, Pendidikan dan Penelitian Ke-Islaman, 2025)
This research aims to describe the classroom management strategies carried out by teachers in class VIII PAI learning at SMPN 1 Lamongan with the research subject being the class VIII PAI teacher. This research uses the research method that the author uses is a qualitative method. Interviews, observation, and documentation are the methods used to collect data. The results of this research show 1. The teacher also has a special strategy in organizing the class, namely by taking notes in a small book. This book is used by teachers to record every detail of class management needs. The teacher also applies one learning technique that is suitable for use in PAI learning, namely a problem-based learning system. The management strategies applied are different for each level and subject, as well as extensive PAI learning management. 2. Factors that help in classroom management are optimal school curriculum, adequate classroom facilities, teachers, students and class dynamics. The inhibiting factors in classroom management are teachers and students. 3. The solution to overcoming obstacles to classroom management in class VIII PAI learning at SMPN 1 Lamongan is for teachers to hold seminars on how to increase teacher creativity in classroom management. Students can be given sanctions if they make mistakes.